2017
DOI: 10.1053/j.seminoncol.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Eviction from the sanctuary: Development of targeted therapy against cell adhesion molecules in acute lymphoblastic leukemia

Abstract: Acute lymphoblastic leukemia (ALL) is a malignant hematological disease afflicting hematopoiesis in the bone marrow. While 80-90% of patients diagnosed with ALL will achieve complete remission at some point during treatment, ALL is associated with high relapse rate, with the 5-year overall survival rate of 68%. The initial remission failure and the high rate of relapse can be attributed to intrinsic chemoprotective mechanisms that allow persistence of ALL cells despite therapy. These mechanisms are mediated, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 174 publications
2
8
0
Order By: Relevance
“…The down-regulated genes were involved in cell division and the cell cycle, while the up-regulated genes were enriched in cell adhesion and regulation of cell differentiation. These data are consistent with other publications that have also reported an increase in cellular adhesion makers in models in which leukemic cells have been cultured with non-malignant adherent cells [18][19][20] . We then conducted a Gene Set Enrichment Analysis (GSEA) to examine the overall expression changes for HALLMARK gene sets defined in MsigDB (FDR q-val < 0.05 and enrichment > 1.5).…”
Section: Resultssupporting
confidence: 93%
“…The down-regulated genes were involved in cell division and the cell cycle, while the up-regulated genes were enriched in cell adhesion and regulation of cell differentiation. These data are consistent with other publications that have also reported an increase in cellular adhesion makers in models in which leukemic cells have been cultured with non-malignant adherent cells [18][19][20] . We then conducted a Gene Set Enrichment Analysis (GSEA) to examine the overall expression changes for HALLMARK gene sets defined in MsigDB (FDR q-val < 0.05 and enrichment > 1.5).…”
Section: Resultssupporting
confidence: 93%
“…Our co-expression analysis revealed that LINC00152 regulates genes involved in substrate cellular adhesion processes, one of the main biological mechanisms associated with relapse and chemoresistance in ALL. Chemoresistance has been addressed in several studies as one of the most important mechanisms of relapse and death in ALL [40][41][42]. Taking together, these data and our findings regarding the association between LINC00152 high expression and the high risk of relapse suggest that LINC00152 could be potentially involved in chemoresistance; however, functional studies are required to prove these remarks.…”
Section: Linc00152 and Linc01013 Expression In Acute Lymphoblastic Leukemiasupporting
confidence: 57%
“…This could involve the suppression of pro-apoptotic factors through various soluble factors, cell adhesion molecules, and extracellular matrix molecules. In fact, previous studies have implicated a range of factors, including CXCL12/CXCR4, NOTCH ligands and receptors, VCAM-1/VLA-4 and 5, fibronectin/VLA-4 and 5, hyaluronate and collagen/CD44 [38,39]. Alternatively, TCL cells may upregulate other Bcl-2 anti-apoptotic proteins to compensate for the loss of Bcl-xL, as observed in patients who developed adaptive resistance after long-term responses to venetoclax [40,41].…”
Section: Discussionmentioning
confidence: 99%